A numerical study on improving the specific properties of staggered composites by incorporating voids. (December 2017) - Mirkhalaf, Mohammad; Ashrafi, Behnam
Graphical abstract: Highlights: Large scale finite element models of staggered composites are developed. Model generations based on random placement and sedimentation of inclusions are followed. It is shown that specific properties can be improved by incorporating voids. 10–30% increase in specific modulus and yield strength can be achieved in polymer matrix composites. Abstract: Despite being porous, natural materials such as bone, nacre and tooth enamel possess interesting combinations of stiffness, strength and toughness, an outstanding performance which is hard to achieve in engineering materials. Recent studies show that this performance is rooted in their architectures in which stiff and strong inclusions are arranged in a staggered structure and placed within a softer matrix. These studies however focus on void-free staggered composites. Here, we use finite element analysis and exhaustive exploration of the design space to show that the specific modulus and yield strength of staggered composites can be improved by removing the non-load bearing regions of the matrix material and to show the morphologies emerging from this process. This improvement increases with aspect ratio of the inclusions and with mismatch of properties between the phases and decreases with inclusion content. Particularly, 20–30% increase in the specific modulus and 10–20% increase in specific yield strength can be achieved considering the actual properties of carbon nanotube (or ceramic/mineral platelet) reinforced polymers. The morphologies emerging from our exploration can be used to develop lightweight composites of interest in aerospace, defence, and packaging industries.